'HVDC optimisation' – driving down the cost of large‐scale offshore wind. Issue 13 (12th December 2017) - Siriwardhana, Kamal; Jackson, Gordon; Canelhas, Andre
Abstract : The cost optimisation of 1‐GW offshore wind farms is investigated in this study. The feasibility of combining AC collector platforms and an HVDC converter platform to form a combined platform is assessed. The evaluation of different electrical connection topologies is undertaken for a wide range of different electrical network configurations that lend themselves to consolidating the number of offshore platforms to reduce capital expenditure and operational expenditure, in order to arrive at a single preferred design option for further optimisation. Both quantitative evaluation based on project net present value and qualitative evaluation of technological aspects such as losses, availability, control/interface, technical complexity and project delivery aspects such as fabrication, yard capacity, transportation and installation are undertaken and ranked.